Preliminary Assessing Species Susceptibity to Climate Change for Terrestrial Vertebrates in Phu Canh Nature Reserve, Hoa Binh Province - Anh, Nguyen Thi Lan; Mai, Doan Huong (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Phu Canh Nature Reserve is located in Da Bac district, Hoa Binh province. The reserve covers an area of 5.647 ha and plays an important role in the conservation of biodiversity resources, in supporting many rare wildlife species with high conservation value. In this nature reserve, we identified 48 reptilian species of 16 families in 2 orders; 28 amphibian species of 6 families in 2 orders; 65 bird species of 24 families in 7 orders; 57 mammal species of 25 families in 8 orders. Many of which are rare, endangered, and listed in the Vietnam Red Data Book, IUCN Red List and Decree 32/2006/ND-CP. Among threatened species, the mammals made up the highest percentage (31.6%) and the amphibians made up the lowest (10.7%). In terms of species that are susceptible to climate change, the amphibians made up the highest percentage (42.8%) while the birds made up the lowest (35.3%). The reptiles made up the relatively high proportion of threatened species (20.9%) and “climate-change-susceptible” species (37.5%), while the percentage of mammals species that were both susceptible and threatened was 38.6%. The amphibians and mammals seem to face their extinction risk if there exist no timely conservation action plans in the area. This is the first data assessing the susceptibility of terrestrial vertebrates to climate change at Phu Canh Nature Reserve.  Keywords: Terrestrial vertebrate, Susceptibility, Climate Change, Phu Canh.